Development of the Chronically Ill Patient Service Model to Reduce Overcrowding in Sub-district Health Promoting Hospitals under Corona virus Disease 2019 Pandemic Situation at Khok Yang Sub-district, Prakhon Chai District, Buri Ram Province - เอ็มประโคน มัธนา (Journal of Health Science of Thailand, 2024)
This research is an action research with the objective of developing a model for chronic disease clinic services in Khok Yang Sub-District Health Promoting Hospital. Under the situation of the outbreak of corona virus disease 2019, the samples in this study were divided into 2 groups: the group 1 was 228 chronic disease patients, selected by purposive sampling, and the group 2 was 100 members of the health network in the area consisted of physician, public health officials, presidents of local government organizations, community leaders, public health volunteers, and community health leaders selected by purposive sampling. The study was conducted from March 2020 to February 2021. Data were collected from the health database system of the service units and focus groups. The research was conducted in 5 steps: (1) situation analysis step, (2) activity planning step, (3) operation and observation step, (4) practice reflection step, and (5) evaluation step. The assessment approach was in accordanc with the guidelines for organizing chronic disease clinic services according to the principles of family medicine and having a family medicine doctor as a consultant. The results of the study revealed that the model for providing chronic disease clinic services consisted of (1) setting up a health station in every village, (2) having village health volunteers provide basic services to patients with chronic diseases, (3) having village health volunteers receive and deliver. medicines for patients at home, (4) improving the service model of chronic disease clinics, and (5) evaluating results for reducing congestion and reducing waiting times for services. The results of the developed model could reduce congestion at health facilities, reduced patient waiting time, and allow patients to receive medication continuously. There was no patient missing medication, which would result in the proper control of the severity of the disease and reduce complications in the patients. It was also found that patients satisfaction was at a highest level (up to 97.36%). The model should be suitable for further development according to the context and problem situation of each area.